Ceramic product and preparation method thereof
By using composite preparation methods of modified clay and other clay materials, the problems of easy cracking and poor stability of ceramic products during processing and decoration are solved, and the high plasticity, excellent mechanical properties and low production costs of ceramic products are achieved.
Patent Information
- Application Number
- CN202410876758.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-02
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-07-02
AI Technical Summary
Existing ceramic products are prone to cracking during processing and decoration, have low strength and poor stability. The traditional preparation methods consume high energy and cost high, making it difficult to meet the demand for mass production.
The composite preparation method of modified clay, wollastonite, talc, kaolin, diopylene, high alumina sand and bentonite is used to improve the dispersion and structural stability of clay particles through the use of modifiers, and reduce the firing temperature and time.
The prepared ceramic products have good plasticity, excellent mechanical properties, are not easy to crack, have good stability, and are low in production costs, and are suitable for mass production.
Smart Images

Figure BDA0004923291450000111 
Figure BDA0004923291450000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic products, and in particular relates to a ceramic product and a preparation method thereof. Background Art
[0002] Rongchang pottery is one of the four famous potteries in my country. It is not only a daily necessity, but also a work of art with profound cultural connotations. Rongchang pottery has unique production technology and artistic style, and is known as "thin as paper, bright as a mirror, and sound like a chime", adding an indispensable page to the history of Chinese ceramics and Chinese arts and crafts.
[0003] The raw materials for the preparation of Rongchang pottery are mostly clay from the Rongchang area, and various products are obtained after fine mixing, shaping and high-temperature firing. However, at present, the traditional preparation process of ceramics mainly relies on clay materials. However, the ceramics made by this method have poor plasticity and are prone to cracking during processing and decoration, such as carving and polishing. The strength is also low, which is inconvenient to transport and easy to damage. At the same time, the stability is poor, and it is easy to break when used as a handicraft or daily necessities for a long time. In addition, the high firing temperature and long firing time lead to energy waste and high costs, which are not conducive to mass production. Summary of the invention
[0004] The object of the present invention is to provide a ceramic product and a preparation method thereof, wherein the production cost of the ceramic product is low, the prepared ceramic product has good plasticity, excellent mechanical properties, is not easy to crack, and has good stability. In order to achieve the above object, the present invention provides the following technical solutions:
[0005] A ceramic product, wherein the raw materials for preparing the ceramic product include, by weight: 50-70 parts of modified clay, 5-15 parts of wollastonite, 8-12 parts of talc, 10-20 parts of kaolin, 5-15 parts of diopside, 12-22 parts of high-alumina sand, and 3-8 parts of bentonite.
[0006] The preparation method of the modified clay comprises the following steps:
[0007] S1. Pretreatment of the original clay: crushing, wet grinding, passing through a 100-200 mesh sieve and drying the clay to a moisture content of ≤20%, sealing and aging for 30-60 days, then taking it out and drying it to a constant weight to obtain the pretreated clay;
[0008] S2, adding water to the pretreated clay, heating to 60-80°C and keeping the temperature for 1-2 hours, collecting the turbid liquid, drying, calcining at 400-500°C for 1-2 hours, and then sieving through a 100-200 mesh sieve to obtain a clay sample;
[0009] S3, taking the modifier and stirring it evenly in a 40-75wt% ethanol aqueous solution to obtain a modifier solution;
[0010] S4. Mix the modifier solution with the clay sample, stir at 70-90°C for 6-8h, add graphite, continue stirring for 1-2h, filter, dry, grind and pass through a 500-800 mesh sieve to obtain modified clay.
[0011] Preferably, the original clay includes clay A and clay B.
[0012] Preferably, the mass ratio of clay A to clay B is 1:(3-5); more preferably, it is 1:4.
[0013] Preferably, the chemical composition (w / %) of the clay A includes: SiO2, 65-75; Al2O3, 13-19; Fe2O3, 2-6; CaO, 0.2-2; MgO, 1-2.5; TiO2, 0.5-1; K2O, 1.6-2.5; Na2O, 1.8-3.5; the remainder is loss on ignition.
[0014] Preferably, the chemical composition (w / %) of the clay B includes: SiO2, 60-70; Al2O3, 10-17; Fe2O3, 6-10; CaO, 0.1-0.3; MgO, 0.7-1; TiO2, 0.7-1; K2O, 1-2.6; Na2O, 0.1-1; the remainder is loss on ignition.
[0015] In some preferred schemes, the clay A can be taken from Gufoshan, and the clay B can be taken from Luoguanshan. The clays from two different regions in Rongchang District are selected to prepare the modified clay, which can improve the plasticity and flexural strength of the prepared clay. This may be because the clays from two different regions not only have different chemical compositions, but also have different organic types, resulting in different bonding properties and strengths of the two clays. They are applied to the preparation of ceramic products, and there is a synergistic effect between the two clays, which improves the plasticity of the ceramics and improves their flexural strength. In addition, both clays are from the local area, which greatly saves the cost of the prepared ceramic products.
[0016] Preferably, in step S2, the solid-to-liquid ratio of the pretreated clay and water is 1 g:40-60 mL.
[0017] Preferably, the amount of the modifier added is 8wt% to 15wt% of the clay sample.
[0018] Preferably, the modifier is isomeric tridecanol polyoxyethylene ether, hexadecyltrimethylammonium bromide, or methyltrimethoxysilane.
[0019] Preferably, the mass ratio of the isomeric tridecanol polyoxyethylene ether, hexadecyltrimethylammonium bromide and methyltrimethoxysilane is 1:(2-4):(1-3); further preferably, it is 1:3:2.
[0020] Preferably, the hydroxyl value of the isomeric tridecanol polyoxyethylene ether is 40-60 mgKOH / g, and the HLB value is 12-14; further preferably, the hydroxyl value of the isomeric tridecanol polyoxyethylene ether is 49-55 mgKOH / g, and the HLB value is 13.5.
[0021] The finer the clay particles, the higher the clay viscosity. However, the fine clay particles have poor dispersion and are easy to agglomerate, resulting in uneven green body particles, which affects the stability and strength of the prepared ceramics. The inventors found that the use of isomeric tridecanol polyoxyethylene ether, hexadecyl trimethylammonium bromide, and methyl trimethoxysilane in a mass ratio of 1: (2-4): (1-3) as modifiers to modify the composite clay can ensure that the clay particles have a small particle size, thereby maintaining their good viscosity and plasticity, while also improving the stability of the prepared ceramic products. This may be because, on the one hand, the isomeric tridecanol polyoxyethylene ether and hexadecyl trimethyl ammonium bromide act together on the surface of clay particles, forming a hydrophilic film on the surface of the particles, reducing their surface tension and making them easier to disperse in water. At the same time, the sea interacts with the negative charges on the surface of the particles to produce repulsion, causing the particles to disperse each other, thereby improving the dispersibility of the clay particles. On the other hand, hexadecyl trimethyl ammonium bromide and methyl trimethoxy silane are compounded, and hexadecyl trimethyl ammonium bromide is intercalated into the clay layer through ion exchange, expanding the interlayer spacing, facilitating the entry of methyl trimethoxy silane into the layer, and avoiding particle agglomeration. The three modifiers work synergistically, and at the same time improve the dispersibility and structural stability of clay particles by physical and chemical means, thereby improving the stability and strength of the prepared ceramic products.
[0022] In some preferred embodiments, the isomeric tridecanol polyoxyethylene ether is purchased from Jiangsu Hai'an Petrochemical Plant.
[0023] Preferably, the solid-to-liquid ratio of the modifier to the ethanol aqueous solution is 1 g:40-60 mL.
[0024] Preferably, the added amount of the graphite is 0.5wt% to 3wt% of the clay sample.
[0025] Preferably, the average particle size of the graphite is 20 to 50 nm, and the specific surface area is 150 to 250 m 2 / g; Further preferably, the average particle size of the graphite is 35nm and the specific surface area is 180m 2 / g.
[0026] In some preferred embodiments, the graphite is purchased from Beijing Dekedaojin Technology Co., Ltd.
[0027] Preferably, the D50 of the wollastonite is 15-25 μm, and the aspect ratio is (10-20):1; further preferably, the D50 of the wollastonite is 21.5 μm, and the aspect ratio is 15:1.
[0028] In some preferred embodiments, the wollastonite is purchased from Shenzhen Haiyang Powder Technology Co., Ltd.
[0029] Preferably, the talc has a whiteness of ≥85%, a MgO content of ≥28%, and a fineness of 325-600 meshes; further preferably, the talc has a whiteness of ≥90%, a MgO content of ≥30%, and a fineness of 500 meshes.
[0030] Preferably, the oil absorption value of the kaolin is 40-80 g / 100 g, the dispersibility is ≤60 μm, and the fineness is 1250-2000 mesh; further preferably, the oil absorption value of the kaolin is 55-60 g / 100 g, the dispersibility is ≤50 μm, and the fineness is 1500 mesh.
[0031] In some preferred embodiments, the talc and kaolin are purchased from Shenzhen Haiyang Powder Technology Co., Ltd.
[0032] Preferably, the SiO2 content in the diopside is ≥ 60%.
[0033] In some preferred embodiments, the diopside is purchased from Lingshou County Antai Mining Co., Ltd.
[0034] Preferably, the mass ratio of the modified clay, wollastonite, talc, kaolin and diopside is (5-7):(0.5-2):(0.8-1.5):(1-2):1; more preferably, it is 12:2:2:3:2.
[0035] In some preferred schemes, some specific wollastonite, talc, kaolin and diopside are selected, and the mass ratio of the modified clay, wollastonite, talc, kaolin and diopside is (5-7): (0.5-2): (0.8-1.5): (1-2): 1, which can further improve the stability of the prepared ceramic products while improving their strength and saving energy. This may be because, on the one hand, wollastonite, diopside and kaolin together constitute the skeleton structure of ceramic products. They are intertwined and fused during the firing process to form a tighter and more stable structure, thereby improving the strength of the product. In addition, the calcium feldspar and quartz generated by the reaction significantly reduce the volume shrinkage rate, thereby ensuring the stability and strength of the ceramic products. On the other hand, the compound of wollastonite and talc can not only produce the mineral phase of clinker at a lower temperature, but also the solid-phase reaction with the modified clay at high temperature promotes the migration and diffusion of substances, which is beneficial to the sintering, and then helps to reduce the firing temperature of the ceramic body, shorten the firing cycle, thereby saving energy and reducing costs.
[0036] Preferably, the density of the high alumina sand is 2.4-2.8 kg / m 3 , hardness is 7-8HB, Al2O3 content is ≥70%; further preferably, the density of the high alumina sand is 2.4-2.8kg / m 3 , hardness is 7~8HB, Al2O3 content ≥70%.
[0037] In some preferred embodiments, the high-alumina sand is purchased from Lingshou County Longde Mineral Products Sales Co., Ltd.
[0038] Preferably, the SiO2 content in the bentonite is 60% to 70%, the plastic viscosity is ≤3, and the filtration loss is ≤15cm 3 ; Further preferably, the SiO2 content in the bentonite is 62% to 67%, the plastic viscosity is ≤2, and the filtration loss is ≤13cm 3 .
[0039] Preferably, the mass ratio of the modified clay to bentonite is (10-15):1; further preferably, it is 12:1.
[0040] In some preferred embodiments, the bentonite is purchased from Anji Runying New Materials Co., Ltd.
[0041] In some preferred schemes, specific bentonite and graphite are selected, and the addition amount of the graphite is 0.5wt% to 3wt% of the clay sample. When the mass ratio of modified clay and bentonite is (10 to 15): 1, the strength of the ceramic product can be improved while improving its plasticity. This may be because graphite and bentonite work synergistically. On the one hand, the specific mineral components enable the particles in the ceramic raw materials to be better combined together. On the other hand, by increasing the electrostatic force and van der Waals force between the particles, the distance between the particles is close, the contact points of the soil particles per unit area become more, and the corresponding original cohesion becomes larger, thereby improving plasticity. At the same time, graphite and bentonite reduce the porosity of ceramic products by physical filling and chemical reaction product filling, respectively, thereby improving the stability and strength of ceramic products. In addition, adding graphite when preparing modified clay can enable graphite to be better dispersed between extremely fine clay particles to avoid agglomeration.
[0042] The second aspect of the present invention provides a method for preparing the ceramic product, comprising the following steps:
[0043] A1. After mixing the raw materials, ball mill and sieve, add water and stir into a paste, filter, store until the mud is clear, pour out the water, and obtain the mud blank;
[0044] A2. Take the clay and knead it repeatedly to make it into a round shape, place it in the center of the blank making car, and after it is formed by throwing, air-dry it to grayish white, and then process and decorate it;
[0045] A3. Sinter the decorated clay to form a ceramic product.
[0046] Preferably, the amount of clean water added is 25wt% to 45wt% of the mud mass.
[0047] Preferably, the processing and decoration include grinding, engraving, glazing and re-grinding.
[0048] Preferably, the sintering conditions are: temperature 1000-1100° C., time 10-20 h.
[0049] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0050] 1. The present invention provides a ceramic product, which uses Rongchang local clay resources as raw materials, reduces production costs, and the prepared ceramic product has good plasticity, excellent mechanical properties, is not easy to crack, and has good stability. It is particularly suitable for preparing Rongchang carved pottery. The firing temperature and firing time are reduced during the preparation process, thereby saving energy and further reducing costs.
[0051] 2. The present invention selects clays from two different regions in Rongchang District to compound and prepare modified clay, which can improve the plasticity and flexural strength of the prepared clay.
[0052] 3. The present invention modifies the composite clay by selecting isomeric tridecanol polyoxyethylene ether, hexadecyltrimethylammonium bromide and methyltrimethoxysilane in a mass ratio of 1:(2-4):(1-3) as modifiers, which can ensure that the clay particles have a small particle size, thereby maintaining their good viscosity and plasticity, and at the same time improve the stability of the prepared ceramic products.
[0053] 4. The present invention selects some specific wollastonite, talc, kaolin and diopside, and the mass ratio of the modified clay, wollastonite, talc, kaolin and diopside is (5-7): (0.5-2): (0.8-1.5): (1-2): 1, which can further improve the stability of the prepared ceramic products while improving their strength and saving energy.
[0054] 5. The present invention selects specific bentonite and graphite, and the addition amount of the graphite is 0.5wt% to 3wt% of the clay sample. When the mass ratio of modified clay to bentonite is (10 to 15):1, the plasticity of ceramic products can be improved while improving their strength. DETAILED DESCRIPTION
[0055] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0056] The raw materials used in the present invention are all commercially available, specifically:
[0057] The chemical composition (w / wt%) of clay A is: SiO2, 65-75; Al2O3, 13-19; Fe2O3, 2-6; CaO, 0.2-2; MgO, 1-2.5; TiO2, 0.5-1; K2O, 1.6-2.5; Na2O, 1.8-3.5; the remainder is the loss on ignition, which comes from Gufoshan.
[0058] The chemical composition (w / wt%) of clay B is: SiO2, 60-70; Al2O3, 10-17; Fe2O3, 6-10; CaO, 0.1-0.3; MgO, 0.7-1; TiO2, 0.7-1; K2O, 1-2.6; Na2O, 0.1-1; the remainder is the loss on ignition, which comes from Luoguan Mountain.
[0059] Isomeric tridecanol polyoxyethylene ether, with a hydroxyl value of 49-55 mgKOH / g and an HLB value of 13.5, was purchased from Jiangsu Hai'an Petrochemical Plant.
[0060] Graphite, average particle size 35nm, specific surface area 180m 2 / g, purchased from Beijing Dekedao Gold Technology Co., Ltd.
[0061] Wollastonite, with a D50 of 21.5 μm and an aspect ratio of 15:1, was purchased from Shenzhen Haiyang Powder Technology Co., Ltd.
[0062] Talc, whiteness ≥ 90wt%, MgO content ≥ 30wt%, fineness 500 mesh; kaolin, oil absorption value 55-60g / 100g, dispersibility ≤ 50μm, fineness 1500 mesh; all purchased from Shenzhen Haiyang Powder Technology Co., Ltd.
[0063] Diopside, SiO2 content ≥ 60wt%, was purchased from Lingshou County Antai Mining Co., Ltd.
[0064] High alumina sand, density is 2.4~2.8kg / m 3 , hardness of 7-8HB, Al2O3 content ≥70wt%, purchased from Lingshou County Longde Mineral Products Sales Co., Ltd.
[0065] Bentonite, SiO2 content is 62wt%~67wt%, plastic viscosity ≤2, filtration loss ≤13cm 3 , purchased from Anji Runying New Materials Co., Ltd.
[0066] Example 1
[0067] The present embodiment provides a ceramic product, and the raw materials for its preparation are, by weight: 60 parts of modified clay, 10 parts of wollastonite, 10 parts of talc, 15 parts of kaolin, 10 parts of diopside, 18 parts of high alumina sand, and 5 parts of bentonite.
[0068] The preparation method of the modified clay comprises the following steps:
[0069] S1. Pretreatment of the original clay: crushing, wet grinding, passing through a 150-mesh sieve, and drying the clay to a moisture content of about 13.5 wt %, sealing and aging the clay for 40 days, and then drying the clay to a constant weight to obtain the pretreated clay;
[0070] S2, adding water to the pretreated clay, heating to 70°C and keeping the temperature for 1.5h, collecting the turbid liquid, drying it, calcining it at 450°C for 1.5h, and then passing it through a 150-mesh sieve to obtain a clay sample;
[0071] S3, taking the modifier into 70wt% ethanol aqueous solution and stirring it evenly to obtain a modifier solution;
[0072] S4. Mix the modifier solution with the clay sample, stir at 80°C for 7 hours, add graphite, continue stirring for 1.5 hours, filter, dry, grind and pass through a 700-mesh sieve to obtain modified clay.
[0073] The clays are clay A and clay B.
[0074] The mass ratio of clay A to clay B is 1:4.
[0075] The solid-to-liquid ratio of the pretreated clay and water in step S2 is 1 g:50 mL.
[0076] The amount of the modifier added was 12 wt % of the clay sample.
[0077] The modifiers are isomeric tridecanol polyoxyethylene ether, hexadecyl trimethylammonium bromide and methyl trimethoxysilane.
[0078] The mass ratio of the isomeric tridecanol polyoxyethylene ether, hexadecyltrimethylammonium bromide and methyltrimethoxysilane is 1:3:2.
[0079] The solid-to-liquid ratio of the modifier to the 70wt% ethanol aqueous solution is 1g:50mL.
[0080] The added amount of graphite is 1.5wt% of the clay sample.
[0081] The method for preparing the ceramic product comprises the following steps:
[0082] A1. After mixing the raw materials, ball mill and sieve, add water and stir into a paste, filter, store until the mud is clear, pour out the water, and obtain the mud blank;
[0083] A2. Take the clay and knead it repeatedly to make it into a round shape, place it in the center of the blank making car, and after it is formed by throwing, air-dry it to grayish white, and then process and decorate it;
[0084] A3. Sinter the decorated clay to form a ceramic product.
[0085] The amount of clean water added is 35wt% of the clay mass.
[0086] The processing decoration is carving.
[0087] The sintering conditions are: temperature 1050° C., time 14 h.
[0088] Example 2
[0089] The difference between this embodiment and embodiment 1 is that the ceramic product is prepared from the following raw materials, by weight: 60 parts of modified clay, 12 parts of wollastonite, 12 parts of talc, 15 parts of kaolin, 12 parts of diopside, 15 parts of high alumina sand, and 6 parts of bentonite.
[0090] Example 3
[0091] The difference between this embodiment and embodiment 1 is that the mass ratio of the isomeric tridecanol polyoxyethylene ether, hexadecyltrimethylammonium bromide and methyltrimethoxysilane is 1:2:1.
[0092] Comparative Example 1
[0093] The difference between this comparative example and Example 1 is that the clay is clay A.
[0094] Comparative Example 2
[0095] The difference between this comparative example and Example 1 is that the modifier is isomeric tridecanol polyoxyethylene ether and hexadecyl trimethyl ammonium bromide;
[0096] The mass ratio of the isomeric tridecanol polyoxyethylene ether to hexadecyltrimethylammonium bromide is 1:3.
[0097] Comparative Example 3
[0098] The difference between this comparative example and Example 1 is that the added amount of the graphite is 0.1wt% of the clay sample.
[0099] Comparative Example 4
[0100] The difference between this comparative example and Example 1 is that the ceramic product is prepared from the following raw materials, by weight: 40 parts of modified clay, 20 parts of wollastonite, 15 parts of talc, 20 parts of kaolin, 15 parts of diopside, 18 parts of high alumina sand, and 5 parts of bentonite.
[0101] Comparative Example 5
[0102] The difference between this comparative example and Example 1 is that the ceramic product is prepared from the following raw materials, by weight: 80 parts of modified clay, 10 parts of wollastonite, 10 parts of talc, 15 parts of kaolin, 10 parts of diopside, 18 parts of high alumina sand, and 5 parts of bentonite.
[0103] Comparative Example 6
[0104] The difference between this comparative example and Example 1 is that the isomeric tridecanol polyoxyethylene ether has a hydroxyl value of 165-175 mgKOH / g and an HLB value of 11.5, and is purchased from Nantong Yongle Chemical Co., Ltd.
[0105] Comparative Example 7
[0106] The difference between this comparative example and Example 1 is that graphite, with an average particle size of 100 nm, was purchased from Ningbo Luofei Nanotechnology Co., Ltd.
[0107] Performance Testing
[0108] The plasticity of ceramic products was tested with reference to Zhu Chenghong's "Ceramic Technology Experiment". The bending strength of ceramic products was tested with reference to GB / T 4741-1999 "Test Method for Bending Strength of Ceramic Materials". The stability of ceramic products was evaluated with reference to the test method for measuring the adaptability of samples from refrigerator to oven in GB / T 3532-2009 "Daily Porcelain". The ceramic products were qualified if they cracked after one cycle from -8℃ to 200℃. The results are shown in Table 1.
[0109] Table 1 Measurement results
[0110]
[0111]
[0112] According to statistics, the ceramic products prepared by Examples 1 to 3 of the present invention have plasticity greater than 3, bending strength greater than 90 MPa, and excellent stability. Comparative Example 1 has only one original clay, Comparative Example 2 does not add methyltrimethoxysilane modifier, Comparative Example 3 has low graphite addition, Comparative Example 4 has too low modified clay addition, Comparative Example 5 has high modified clay addition, Comparative Example 6 uses isomeric tridecanol polyoxyethylene ether with too high hydroxyl value and too low HLB value, and Comparative Example 7 has too high graphite average particle size. The prepared ceramic products have poor performance. Therefore, the ceramic products prepared by the raw materials and methods described in this application have good plasticity, excellent mechanical properties, are not easy to crack, and have good stability, and are particularly suitable for preparing Rongchang carved pottery.
[0113] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A ceramic product, characterized in that: The raw materials for its preparation include, by weight: 50-70 parts of modified clay, 5-15 parts of wollastonite, 8-12 parts of talc, 10-20 parts of kaolin, 5-15 parts of diopside, 12-22 parts of high-alumina sand, and 3-8 parts of bentonite; The preparation method of the modified clay comprises the following steps: S1. Pretreatment of the original clay: crushing, wet grinding, passing through a 100-200 mesh sieve and drying the clay to a moisture content of ≤20%wt%, sealing and aging for 30-60 days, taking it out and drying it to a constant weight to obtain the pretreated clay; S2, adding water to the pretreated clay, heating to 60-80°C and keeping the temperature for 1-2 hours, collecting the turbid liquid, drying it, calcining it at 400-500°C for 1-2 hours, and then passing it through a 100-200 mesh sieve to obtain a clay sample; S3, taking the modifier and stirring it in a 40-75wt% ethanol aqueous solution to obtain a modifier solution; S4, taking the modifier solution and mixing it with the clay sample, stirring it at 70-90°C for 6-8h, adding graphite, continuing to stir for 1-2h, filtering, drying, grinding and passing through a 500-800 mesh sieve to obtain modified clay; The original clay includes clay A and clay B; The mass ratio of clay A to clay B is 1:(3-5); The chemical composition (w / %) of the clay A includes: SiO2, 65-75; Al2O3, 13-19; Fe2O3, 2-6; CaO, 0.2-2; MgO, 1-2.5; TiO2, 0.5-1; K2O, 1.6-2.5; Na2O, 1.8-3.5; the remainder is the loss on ignition; The chemical composition (w / %) of the clay B includes: SiO2, 60-70; Al2O3, 10-17; Fe2O3, 6-10; CaO, 0.1-0.3; MgO, 0.7-1; TiO2, 0.7-1; K2O, 1-2.6; Na2O, 0.1-1; the remainder is the loss on ignition; The amount of the modifier added is 8wt% to 15wt% of the clay sample; The modifiers are isomeric tridecanol polyoxyethylene ether, hexadecyl trimethyl ammonium bromide and methyl trimethoxy silane; The mass ratio of the isomeric tridecanol polyoxyethylene ether, hexadecyltrimethylammonium bromide and methyltrimethoxysilane is 1:(2-4):(1-3); the hydroxyl value of the isomeric tridecanol polyoxyethylene ether is 40-60 mgKOH / g, and the HLB value is 12-14.
2. The ceramic product according to claim 1, characterized in that The added amount of the graphite is 0.5wt% to 3wt% of the clay sample.
3. The ceramic product according to claim 1, characterized in that The average particle size of the graphite is 20-50 nm, and the specific surface area is 150-250 m 2 / g.
4. The ceramic product according to claim 1, characterized in that The D50 of the wollastonite is 15-25 μm, and the aspect ratio is (10-20):
1.
5. The ceramic product according to claim 1, characterized in that: The talc has a whiteness of ≥85%, a MgO content of ≥28%, and a fineness of 325-600 meshes.
6. The ceramic product according to claim 1, characterized in that: The kaolin has an oil absorption value of 40 to 80 g / 100 g, a dispersibility of ≤60 μm, and a fineness of 1250 to 2000 meshes.
7. The ceramic product according to any one of claims 1 to 6, characterized in that: The mass ratio of the modified clay, wollastonite, talc, kaolin and diopside is (5-7): (0.5-2): (0.8-1.5): (1-2):
1.
8. The ceramic product according to claim 7, characterized in that The SiO2 content in the bentonite is 60wt% to 70wt%, the plastic viscosity is ≤3, and the filtration loss is ≤15cm 3 .
9. The method for preparing a ceramic product according to claim 8, characterized in that: The mass ratio of the modified clay to bentonite is (10-15):
1.
10. A method for preparing a ceramic product according to any one of claims 1 to 9, characterized in that: The following steps are involved: A1. After mixing the raw materials, ball mill and sieve, then add clean water and stir into a paste, filter, store until the mud is clear, pour out the clean water, and obtain the mud blank; A2. Take the clay and knead it repeatedly to make it into a round shape, place it in the center of the blank making car, and after it is formed by throwing, air-dry it to grayish white, and then process and decorate it; A3. Sinter the decorated clay to form a ceramic product.
Citation Information
Patent Citations
Electrical ceramic used for electronic components and preparation method thereof
CN107963877A
Modified composite clay and manufacturing method thereof
CN109020476A